Malnourished patients on hemodialysis improve after receiving a nutritional intervention - Calegari,Adaiane (2011)
INTRODUCTION: Malnutrition is multifactorial and may be modified by nutritional intervention. We aimed to assess the impact of an intervention on the nutritional status of malnourished hemodialysis patients and their acceptance of a non-industrialized nutritional supplement. METHODS: 18 patients were studied, they were selected from a previous nutritional assessment where nutritional risk was defined as: subjective global assessment > 15 plus one criterion for malnutrition. The following variables were assessed: anthropometric parameters, subjective global assessment, dietary intake, six-minute walking test, quality of life (SF-36), and biochemical tests. Patients were randomized to either Control or Intervention Groups. The Intervention Group received a dietetic supplement during dialysis containing 355 kcal, prepared from simple ingredients. After three months, subjects from the Control Group and other patients also considered at nutritional risk underwent the same intervention. The study groups were compared after three months, and all patients were analyzed before and after the intervention. RESULTS: Fifteen men and three women, aged 56.4 ± 15.6 years-old, nine in each group, were studied. The Intervention Group showed an improvement in the subjective global assessment (p = 0.04). There were differences in role physical and bodily pain domains of SF-36, with improvement in the Intervention Group and worsening in the Control Group (p = 0.034 and p = 0.021). Comparisons before and after intervention for all patients showed improvement in the subjective global assessment (16.18 ± 4.27 versus 14.37 ± 4.20, p = 0.04), and in the six-minute walking test (496.60 ± 132.59 versus 547.80 ± 132.48 m; p = 0.036). The nutritional supplement was well tolerated by all patients, and it did not cause side effects. CONCLUSIONS: The nutritional intervention improved the subjective global assessment and quality of life of hemodialysis patients at short-term. A global intervention by a dietitian produced specific and nonspecific positive effects in the whole group. Nutritional supplementation was feasible, palatable, and had low cost. Its clinical impact and effectiveness need to be further assessed in a larger group of patients at long-term.